Production system and challenges of saline aquaculture in Punjab and Sindh provinces of Pakistan - Rossignoli, C. M.; Obi, C.; Ali, S. A.; Ullah, Najeeb; Khalid, Sidra; Hafeez, Mohsin; Shah, Syed Mehtab Hassan (Frontiers Media, 2023)
Introduction: Lack of data about saline aquaculture in Pakistan has curtailed informed policy and investment decision making resulting in undervaluation of and underinvestment in the sector. Therefore, saline aquaculture in Pakistan is today an underdeveloped sector despite its potential as an alternative livelihood for the country's rural farmers. This study represents one of the initial exploratory investigations into saline aquaculture systems in Pakistan, aiming to comprehend the existing sectoral landscape, production challenges, post-harvest constraints, and the associated capacity and investment needs. Methods: The study employed purposive sampling to survey 121 low-income saline aquaculture farmers across five districts of Southern Punjab and Sindh provinces. The analysis was carried out using descriptive statistics. Results: The results revealed that the saline aquaculture sector is predominantly male-centric, with agricultural land utilized for both agriculture and aquaculture purposes. Ponds, which usually serve multiple functions, focus primarily on carp production, but adherence to good management practices remains limited. Farmers face various challenges, including the high costs of feed and seeds, freshwater scarcity, inadequate technical knowledge, and marketing issues. Discussion and conclusion: This study serves as a foundational assessment, addressing data and information gaps crucial for supporting the sustainable development of saline aquaculture in Pakistan. To facilitate such development, the study recommends initiating programs to strengthen technical skills in saline aquaculture, together with the establishment of hatcheries and breeding stations for saline-tolerant species, aiming to reduce dependence on freshwater species in saline pond environments.